Leukocyte Expression of Type 1 and Type 2 Purinergic Receptors and Pro-Inflammatory Cytokines during Total Sleep Deprivation and/or Sleep Extension in Healthy Subjects - Chennaoui, Mounir; Arnal, Pierrick J.; Drogou, Catherine; Leger, Damien; Sauvet, Fabien; Gomez-Merino, Danielle (Frontiers in Neuroscience, 2017)
The purinergic type P1 (adenosine A1 and A2A) receptors and the type P2 (X7) receptor have been suggested to mediate physiological effects of adenosine and adenosine triphosphate on sleep. We aimed to determine gene expression of A1R (receptor), A2AR and P2RX7 in leukocytes of healthy subjects during total sleep deprivation followed by sleep recovery. Expression of the pro-inflammatory cytokines IL-1β and TNF-α were also determined as they have been characterized as sleep regulatory substances, via P2RX7 activation. Blood sampling was performed on 14 young men (aged 31.9 ± 3.9) at baseline (B), after 24 h of sleep deprivation (24h-SD), and after one night of sleep recovery (R). We compared gene expression levels after six nights of habitual (22.30 – 07.00) or extended (21.00 – 07.00) bedtimes. Using quantitative real-time PCR, the amount of mRNA for A1R, A2AR, P2RX7, TNF-α and IL-1β was analyzed. After 24h-SD compared to B, whatever prior sleep condition, a significant increase of A2AR expression was observed that returned to basal level after sleep recovery (day main effect, F(2,26) = 10.8, p<0.001). In both sleep condition, a day main effect on P2RX7 mRNA was observed (F(2,26) = 6.7, p=0.005) with significant increases after R compared with 24h-SD. TNF-α and IL-1β expressions were not significantly altered. Before 24-h SD (baseline), the A2AR expression was negatively correlated with the latency of stage 3 sleep during the previous night, while that of the A1R positively. This was not observed after sleep recovery following 24-h SD. This is the first study showing increased A2AR and not A1 gene expression after 24-h SD in leukocytes of healthy subjects, and this even if bedtime was initially increased by 1.5 hours per night for six nights. In conclusion, prolonged wakefulness induced an up-regulation of the A2A receptor gene expression in leukocytes from healthy subjects. Significant correlations between baseline expression of A1 and A2A receptors in peripheral cells and stage 3 sleep suggested their involvement in mediating the effects of adenosine on sleep.